Five plays : Ivanov, the seagull, Uncle Vanya, three sisters, and the cherry orchard - Chekhov, Anton Pavlovich (Oxford world's classics., 1998)
Chekhov's worldwide reputation as a dramatist rests on five great plays: Ivanov, The Seagull, Uncle Vanya, Three Sisters, and The Cherry Orchard. All are presented in this collection, taken from the authoritative Oxford Chekhov, in Ronald Hingley's acclaimed translation. Hingley has also written an introduction specifically for this volume in which he provides a detailed history of Chekhov's involvement in the theater and an assessment of his accomplishment as a dramatist.